NMDA Receptors in Retrosplenial Cortex Are Necessary for Retrieval of Recent and Remote Context Fear Memory - Corcoran, Kevin A.; Donnan, Michael D.; Tronson, Natalie C.; Guzmán, Yomayra F.; Gao, Can; Jovasevic, Vladimir; Guedea, Anita L.; Radulovic, Jelena (The Journal of neuroscience, 2011)
Over time, memory retrieval is thought to transfer from the hippocampus to a distributed network of neocortical sites. Of these sites, the retrosplenial cortex (RSC) is robustly activated during retrieval of remotely acquired, emotionally valenced memories. It is unclear, however, whether RSC is specifically involved in memory storage or retrieval, and which neurotransmitter receptor mechanisms serve its function. We addressed these questions by inhibiting NMDARs in RSC via infusions of APV before tests for context fear in mice. Anterior cingulate cortex (ACC) and dorsal hippocampus (DH), which have been implicated in the retrieval of remote and recent memory, respectively, served as neuroanatomical controls. Surprisingly, infusion of APV only into RSC, but not ACC or DH, abolished retrieval of remote memory, as revealed by lack of freezing to the conditioning context. APV infused into RSC also impaired retrieval of recent memory, but had no effect on conditioning or memory storage. Within-subject experiments confirmed that the role of RSC in memory retrieval is not time limited. RSC-dependent context fear memory retrieval was mediated by NR2A, but not NR2B, subunit-containing NMDARs. Collectively, these data are the first demonstration that NMDARs in RSC are necessary for the retrieval of remote and recent memories of fear-evoking contexts. Dysfunction of RSC may thereby contribute significantly to the reexperiencing of traumatic memories in patients with posttraumatic stress disorder.